2001
DOI: 10.2460/ajvr.2001.62.991
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of ducks to avian pneumovirus of turkey origin

Abstract: Ducks inoculated with APV of turkey origin may not develop clinical signs of disease, but they are suspected to play a role as nonclinical carriers of APV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Indeed, the experimental infection of SPF turkeys by the intranasal route with duck APV-C isolates was followed by an APV-C-specific seroconversion, which demonstrates that duck APV-C isolates are indeed infectious for turkeys [24]. The converse experiments have also demonstrated that US APV-C isolates from turkeys are infectious for ducks [25,26]. Altogether, the present study reveals a greater heterogeneity than expected among the G genes of subgroup C APVs and calls for further study of the epidemiological significance of these genetic lineages, both in the United States and in Europe.…”
Section: Resultsmentioning
confidence: 94%
“…Indeed, the experimental infection of SPF turkeys by the intranasal route with duck APV-C isolates was followed by an APV-C-specific seroconversion, which demonstrates that duck APV-C isolates are indeed infectious for turkeys [24]. The converse experiments have also demonstrated that US APV-C isolates from turkeys are infectious for ducks [25,26]. Altogether, the present study reveals a greater heterogeneity than expected among the G genes of subgroup C APVs and calls for further study of the epidemiological significance of these genetic lineages, both in the United States and in Europe.…”
Section: Resultsmentioning
confidence: 94%
“…Current methods used to detect aMPV subtype C infections, such as virus isolation, positive RT-PCR and detection of aMPV-C-specific antibodies, have demonstrated infection in several wild bird species, including rock pigeons, Canadian geese, blue-winged teals, swallows, house sparrows, ring-billed gulls, Muscovy, Pekin ducks, mallards and ostriches Shin et al, 2000Shin et al, , 2001Bennett et al, 2002Bennett et al, , 2004Turpin et al, 2003Turpin et al, , 2008. Thus, studies involving other aMPV subtypes, especially subtype C, in the Brazilian wild bird population are still needed.…”
Section: Discussionmentioning
confidence: 98%
“…In support of this, aMPV-C antibodies or viral RNA were detected in many wild avian species, including American coots, American crows, Canada geese, cattle egrets, rock pigeons, blue-winged teal, wild geese, wild ducks and mallard ducks (Shin et al, 2000Bennett et al, 2002Bennett et al, , 2004Bennett et al, , 2005Turpin et al, 2008;Velayudhan et al, 2008;Padhi & Poss, 2009). The ability of aMPV-C viruses to infect and replicate in ducks has also been reported, suggesting that isolates from poultry can infect this avian species (Shin et al, 2001). In Brazil, where only subtypes A and B have been detected, the role of wild and synanthropic birds in the epidemiology of SHS is not yet clear, nor is it known whether the aMPV A and B subtypes can be isolated from these avian species.…”
Section: Introductionmentioning
confidence: 95%
“…aMPVs cause an acute upper respiratory disease characterized by coughing, nasal discharge, tracheal rales, foamy conjunctivitis, and sinusitis that have been reported principally in turkeys; but cases have been identified in chickens, ducks, pheasants, and guinea fowl (3,7,9,21). The first cases were described in turkeys in South Africa in 1978, and the causative agent was isolated and identified as a pneumovirus in 1986 in Europe (4,14,17).…”
mentioning
confidence: 99%
“…Much of the research in the United States has focused on turkey and wild birds, while little attention has been focused on farm-raised ducks and geese. The presence of the virus in experimentally infected ducks and the recent isolation of aMPV from wild geese demonstrate that these birds may also harbor the virus (21,22). A quick and inexpensive test is needed to determine the infection status of domestic geese and ducks.…”
mentioning
confidence: 99%